2016
DOI: 10.1109/lra.2015.2509024
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning Approach to Visual Perception of Forest Trails for Mobile Robots

Abstract: We study the problem of perceiving forest or mountain trails from a single monocular image acquired from the viewpoint of a robot traveling on the trail itself. Previous literature focused on trail segmentation, and used low-level features such as image saliency or appearance contrast; we propose a different approach based on a deep neural network used as a supervised image classifier. By operating on the whole image at once, our system outputs the main direction of the trail compared to the viewing direction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
425
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 602 publications
(431 citation statements)
references
References 30 publications
0
425
0
6
Order By: Relevance
“…Barnes et al [3] and Oliveira et al [24] provide more recent examples of deep learning used to segment image pixels into drivable routes, which can then be used for planning. While we focus on supervised learning of collision probability, there are many other ways to map between images and actions, including end-to-end neural networks [6,19], affordance-based representations [7], reinforcement learning using either simulated or real images [23,31], and classification of paths from manually collected data [11]. While it would be impossible to survey the vast literature on visual navigation here, we note that these examples and many others do not explicitly address uncertainty about the learned model.…”
Section: Related Workmentioning
confidence: 99%
“…Barnes et al [3] and Oliveira et al [24] provide more recent examples of deep learning used to segment image pixels into drivable routes, which can then be used for planning. While we focus on supervised learning of collision probability, there are many other ways to map between images and actions, including end-to-end neural networks [6,19], affordance-based representations [7], reinforcement learning using either simulated or real images [23,31], and classification of paths from manually collected data [11]. While it would be impossible to survey the vast literature on visual navigation here, we note that these examples and many others do not explicitly address uncertainty about the learned model.…”
Section: Related Workmentioning
confidence: 99%
“…More recently, Giusti et al (Giusti et al, 2016) showed that a monocular system can be trained to follow a hiking path. But once again, only 2D movement is approached, asking a UAV going forward to change its yaw based on likeliness to be following a traced path.…”
Section: Monocular Vision Based Sense and Avoidmentioning
confidence: 99%
“…Originally invented for computer version, CNN models have subsequently been shown to be effective for many different problems including, Simultaneous Localization and Mapping(SLAM) [8], Decision Making [9] and Automatic Driving [10].…”
Section: Convolutional Neural Networkmentioning
confidence: 99%